2022
DOI: 10.3390/antibiotics11010101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Piperacillin-Tazobactam Dosage Regimens on Synergy of the Combination with Tobramycin against Pseudomonas aeruginosa for the Pharmacokinetics of Critically Ill Patients in a Dynamic Infection Model

Abstract: We evaluated piperacillin-tazobactam and tobramycin regimens against Pseudomonas aeruginosa isolates from critically ill patients. Static-concentration time-kill studies (SCTK) assessed piperacillin-tazobactam and tobramycin monotherapies and combinations against four isolates over 72 h. A 120 h-dynamic in vitro infection model (IVM) investigated isolates Pa1281 (MICpiperacillin 4 mg/L, MICtobramycin 0.5 mg/L) and CR380 (MICpiperacillin 32 mg/L, MICtobramycin 1 mg/L), simulating the pharmacokinetics of: (A) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Mechanism-based modeling experiments revealed that tobramycin disrupts the OM and consequently increases accumulation of the partner BL at the target site . It is also in part caused by both BL and tobramycin eliciting their antibacterial action by inhibiting cell wall and protein synthesis, respectively. , Meanwhile, the guanidinylated amphiphilic derivatives 5 and 8 , which are devoid of antibacterial activity, selectively permeabilize the OM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanism-based modeling experiments revealed that tobramycin disrupts the OM and consequently increases accumulation of the partner BL at the target site . It is also in part caused by both BL and tobramycin eliciting their antibacterial action by inhibiting cell wall and protein synthesis, respectively. , Meanwhile, the guanidinylated amphiphilic derivatives 5 and 8 , which are devoid of antibacterial activity, selectively permeabilize the OM.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also displayed the effectiveness of tobramycin with piperacillin/tazobactam and in vitro synergy with ceftazidime/avibactam . The synergistic interaction is presumed to arise from the ability of the aminoglycosides to disrupt the outer membrane (OM) and enhance the periplasmic concentration of the BL antibiotic. , The inclusion of an OM permeabilizing adjuvant based on membrane-acting agents such as aminoglycosides and polymyxins has also been investigated. OM permeabilizers in the form of tobramycin conjugates have been reported to synergize with BL antibiotics such as piperacillin, aztreonam, cephalosporins, and carbapenems. ,,, These hybrid molecules consist of a secondary domain linked to tobramycin via an alkyl tether and lack ribosomal binding activity with the C -5 position used as a point of attachment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Piperacillin and tazobactam combination covers P. aeruginosa and H. influenzae. 16 Treatment success with antibiotics can be defined as a reduction in dyspnea and sputum purulence. 2 The GOLD guidelines developers recommend amoxicillin with clavulanic acid as a first-line option.…”
Section: Antibioticsmentioning
confidence: 99%
“…S. pneumoniae and H. influenzae are sensitive to amoxicillin 15. Piperacillin and tazobactam combination covers P. aeruginosa and H. influenzae 16. Treatment success with antibiotics can be defined as a reduction in dyspnea and sputum purulence 2…”
Section: Antibioticsmentioning
confidence: 99%